Permasalahan Sosial Politik Pada Novel 86 Karya Okky Madasari Dalam Analisis Sosial Gillin dan Gillin - Dian Mufitasari; Ariesma Setyarum (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Social life is inseperable from social interaction. This raises social problems in terms of cultural, religious, economic, educational, and politacal diversity. This research aims to reveal social criticism regarding socio-political problems correlated with Gillin and Gillin’s theory of social problems in novel 86 by Okky Madasari. The method used is descriptive qualitative method. The results of this study reveal three main issues of socio-political problems namely corruption, collusion, and nepotism. The most correlated influence is on economy, habits, and morals. However religion, education, and family issues are also related to these three elements. Economic problems are related to education, habits, religion, and family which have an impact on human behavior. The problem of habits is related to economics, education, morals, and religion which have an impact on the development of society. Moral issues are related to religion, habits, and education which have an impact on the character building of individuals or grups.